Getting ready for a basic accounting examination! / Khashi'ah Yusof - Yusof, Khashi'ah (Kolej Cempaka Kenanga, UiTM Shah Alam, 2000)
For most students examinations are no fun time! Students feel they are under considerable pressure, as they are required to condense the knowledge they have gained into the three hours time frame of the examination. This article is written primarily for the benefit of Diploma in Accountancy students doing basic accounting. Students from other discipline of studies sitting for their basic accounting examination can also benefit from this article. This article will focus on the preparation of financial statements for a trading business namely the Trading and Profit and Loss Accounts and the Balance Sheet at year-end. Some year-end adjustments must also be taken into account when preparing the trader's financial statements. However, this article will only cover two aspects of the year-end adjustments. First adjustment is providing for depreciation for fixed assets. Second adjustments are writing off bad debts and providing for doubtful debts for debtors.